PEMIKIRAN PENDIDIKAN NURCHOLISH MADJID DALAM KONTEKS PENDIDIKAN MULTIKULTURAL - Syaifulloh, Ahmad (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2020)
Education has an important role in shaping a person's character and personality. One of the Islamic intellectual figures who made a major contribution to educational thinking was Nurcholish Majid. He is known as a contemporary Islamic thinker who provides fresh and relevant thoughts, especially in the context of multicultural education. Qualitative research methods are used to explore and describe the essence of his educational thinking and its impact in the context of modern education. This research method will involve analysis of Nurcholish Majid's texts, interviews with thought experts, and case studies of the implementation of his educational concepts in educational institutions. The data analysis technique used is descriptive analysis technique. The results of this research are the multicultural-pluralistic concept of religious education (Islam) initiated by Nurcholish Madjid as starting point from the philosophicalanthropological concept of humans as 'Abd Allah and caliph of Allah whose human qualities have not been completed (processed) so that they require struggle (mujahadah) to perfect them through understanding. and correct religious education, which can understand the essence and purpose of the religion prescribed by the law.